Pemanfaatan Sampah Plastik Menjadi Bahan Bakar Minyak Dengan Proses Pirolisasi BSB Di Desa Kasilib Wanadadi Banjarnegara - Nur Farida; Mukhamad Agil Ikhsanudin; Rohmat Safrudin; Ismatun Choeriyah; Ismi Rodhliatul Walidaen; Nabila Zakia Fatimah; Zaef Nur Faizin; Fadhilah Azzafira Labibah; Arum may Saroh; Vallen Muda Khariza Rizqi; Nanda Isnaeni Rizki; Ambar Prawati; Ning Ayu Laeli Wahyuni; Latif Maulana Yusuf (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The handling of plastic waste in Indonesia, especially in Central Java, poses a serious issue. Bank Sampah Banjarnegara (BSB) in Kasilib Village, Wanadadi, Banjarnegara, stands as a successful example in addressing this problem. The motivation from the increasing plastic waste prompted BSB to seek innovative solutions. Through the Fastpol 5.0 technology, BSB successfully converted plastic waste into high-efficiency fuel oil. Fastpol 5.0, a fifth-generation pyrolysis machine, can transform plastic waste through the fast pyrolysis and catalytic cracking processes. The machine excels in efficiency, the ability to produce various types of fuel, and plasma technology to clean combustion residues. This innovation is acknowledged through the nomination for the 2023 Innovative Government Award (IGA). BSB not only prioritizes economic aspects but also considers the environmental and public health impacts. Collaboration with waste collectors is a holistic approach to managing plastic waste. In addition to Fastpol 5.0, BSB has also developed a practical kerosene stove in the hope of providing economic and environmental solutions. The success of BSB demonstrates that technology-based solutions can be a positive step in handling plastic waste. It is recommended for these solutions to be adopted by other regions while increasing public awareness of waste separation. Environmental sustainability can be achieved through technological innovations that are not only effective but also have positive economic and social impacts.